Driving Digital Finance in Startups: The Mediating Effects of Corporate Governance, Financial Literacy, and Technological Innovation - Gultom, Hamonangan Justinus (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The rapid digital transformation of financial systems has become critical for startup competitiveness in emerging economies. This study examines the influence of financial inclusion and taxation on digital finance in Indonesian startups, with corporate governance, financial literacy, and technological innovation as mediating variables. Using a quantitative approach with Structural Equation Modeling (SEM), the study surveyed 100 startups as respondents. The results indicate that financial inclusion significantly affects corporate governance, financial literacy, technological innovation, and digital finance. Taxation is also shown to influence financial literacy, technological innovation, and the adoption of digital finance. The mediating variables governance, literacy, and innovation play an essential role in strengthening the relationship between financial inclusion, taxation, and digital finance. The findings highlight that digital finance is shaped not only by access to capital and tax regulations but also by a firm’s internal capacity to strengthen governance, enhance literacy, and adopt innovative technologies. The study contributes theoretically by expanding the discourse on digital financial transformation, and practically by offering insights for policymakers, financial institutions, and business actors to promote transparency, accountability, and competitiveness in the digital economy.The rapid digital transformation of financial systems has become critical for startup competitiveness in emerging economies. This study examines the influence of financial inclusion and taxation on digital finance in Indonesian startups, with corporate governance, financial literacy, and technological innovation as mediating variables. Using a quantitative approach with Structural Equation Modeling (SEM), the study surveyed 100 startups as respondents. The results indicate that financial inclusion significantly affects corporate governance, financial literacy, technological innovation, and digital finance. Taxation is also shown to influence financial literacy, technological innovation, and the adoption of digital finance. The mediating variables governance, literacy, and innovation play an essential role in strengthening the relationship between financial inclusion, taxation, and digital finance. The findings highlight that digital finance is shaped not only by access to capital and tax regulations but also by a firm’s internal capacity to strengthen governance, enhance literacy, and adopt innovative technologies. The study contributes theoretically by expanding the discourse on digital financial transformation, and practically by offering insights for policymakers, financial institutions, and business actors to promote transparency, accountability, and competitiveness in the digital economy.